Reparação óssea em alvéolos de ratas ovarectomizadas após implante com biovidro: análise histomorfométrica e imunoistoquímica - Azenha, Marcelo Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Objectives: To evaluate the process of alveolar repair in ovariectomized rats after implantation with Biosilicate. Materials and Methods: Sixty rats were divided into four groups (n = 15) according to treatment: Group 1 - rats underwent sham surgery with alveoli filled with blood clot; Group 2 - rats underwent sham surgery with alveoli filled with crystalline Biosilicate; Group 3 - ovariectomized rats with alveoli filled with blood clot; Group 4 - ovariectomized rats with alveoli filled with crystalline Biosilicate. After 7, 14 and 28 days the animals were sacrificed and histomorphometric analysis (histology and histometric) and immunohistochemical (Osteopontin and Osteocalcin) were measured . The comparison of the results was performed using the statistical program Assistat 2013 for Windows by Analysis of Variance and Mann-Whitney tests, with significant results being found when p ≤ 0:05 . Results: During the 7- day period, Groups 1 and 3 showed better and significantly higher results in bone formation than Groups 2 and 4 (p<0.05). After 14 days the statistical differences remained between Groups 1 and 3 and Groups 2 and 4 (p<0,05). At 28 days, the statically difference remained significant between the same Groups, while the groups implanted with Biosilicate presented about 60% of the socket filled by new bone. Immunohistochemistry revealed expression of proteins osteocalcin and osteopontin, especially in animals subjected to ovariectomy surgery. Conclusions: Groups 1 and 3 were those with the best results throughout the study, with the crystalline Biosilicate presenting favorable result in bone repair without bioglass resorption. The immunohistochemical analysis showed that animals subjected to ovariectomy had a higher signaling in Ostecalcina and Osteopontin proteins

Objetivos: Avaliar o processo de reparo alveolar em ratas ovarectomizadas após implante com Biosilicato cristalino. Materiais e Métodos: Sessenta ratas foram divididas em quatro grupos (n = 15) de acordo com o tratamento: Grupo 1- ratas submetidas à cirurgia sham com alvéolos preenchidos com coágulo; Grupo 2-ratas submetidas à cirurgia sham com alvéolos preenchidos com Biosilicato cristalino; Grupo 3-ratas ovarectomizadas com alvéolos preenchidos com coágulo; e Grupo 4- ratas ovarectomizadas com alvéolos preenchidos com Biosilicato cristalino. Após 7, 14 e 28 dias os animais foram sacrificados e análises histomorfométricas (histologia e histometria) e imunoistoquímicas (Osteopontina e Osteocalcina) foram realizadas. A comparação dos resultados foi realizada utilizando o programa estatístico Assistat 2013 para Windows através da Análise de Variância e teste de Mann-Whitney, com resultados significantes sendo encontrados quando p≤0.05. Resultados: No período de 7 dias, os Grupos 1 e 3 apresentaram resultados superiores e estatisticamente maiores do que os Grupos 2 e 4 (p<0.05) quanto à formação óssea. Após o período de 14 dias as diferenças estatísticas mantiveram-se, com os Grupos 1 e 3 apresentando diferença estatisticamente significante maiores aos Grupos 2 e 4 (p<0.05). Aos 28 dias, a diferença estatística significativa permaneceu entre os mesmo Grupos estudados, sendo que nos grupos implantados com o Biosilicato cerca de 60% do alvéolo já havia sido preenchido por osso novo. A imunoistoquímica revelou expressão das proteínas Osteocalcina e Osteopontina, principalmente nos animais submetidos à cirurgia de ovarectomia. Conclusões: Os Grupos 1 e 3 foram os que apresentaram os melhores resultados durante todo o estudo, com o Biosilicato cristalino apresentando resultado favorável na reparação...
Keywords: Silicatos; Osteoporose; Imuno-histoquímica; Silicates